Monitoring managers: does it matter? - Francesca Cornelli; Zbigniew Kominek; Alexander Ljungqvist (Fondazione Eni Enrico Mattei (FEEM), 2010)
We test under what circumstances boards discipline managers and whether such interventions improve performance. We exploit exogenous variation due to the staggered adoption of corporate governance laws in formerly Communist countries coupled with detailed 'hard' information about the board's performance expectations and 'soft' information about board and CEO actions and the board's beliefs about CEO competence in 473 mostly private-sector companies backed by private equity funds between 1993 and 2008. We find that CEOs are fired when the company underperforms relative to the board's expectations, suggesting that boards use performance to update their beliefs. CEOs are especially likely to be fired when evidence has mounted that they are incompetent and when board power has increased following corporate governance reforms. In contrast, CEOs are not fired when performance deteriorates due to factors deemed explicitly to be beyond their control, nor are they fired for making 'honest mistakes.' Following forced CEO turnover, companies see performance improvements and their investors are considerably more likely to eventually sell them at a profit.
Keywords: G34; G24; G32; K22; O16; P21; 330; Corporate Governance; Large Shareholders; Boards of Directors; CEO Turnover; Legal Reforms; Transition Economies; Private Equity; Corporate Governance; Führungskräfte; Investmentfonds; Private Equity; Transformationsstaaten; Ostmitteleuropa